A new species Chrysorithrum duda (Lepidoptera: Erebidae) from China - Saldaitis, Aidas; Ivinskis, Povilas; Rimsaite, Jolanta (Zootaxa, 2014)
A new noctuid moth, Chrysorithrum duda sp. n., from southwest China is described. Previously the genus Chrysorithrum (Butler 1878) included two species with eastern Palaearctic and Manchurian distributions. The new species differs in appearance, genitalia and DNA from its congeners Chrysorithrum flavomaculata (Bremer) and Chrysorithrum amata (Bremer & Grey).